Toxinotype A Clostridium perfringens causing septicaemia with intravascular haemolysis: two cases and review of the literature. (February 2022) - Woittiez, N.J.C.; van Prehn, J.; van Immerseel, F.; Goossens, E.; Bauer, M.P.; Ramspek, C.L.; Slangen, R.M.E.; Purmer, I.M.; Ludikhuize, J.
Highlights: Clostridium perfringens infection with intravascular haemolysis is rare. Mortality remains 80%. In the literature, polymerase chain reaction toxinotyping is described in only four cases: all toxinotype A. Toxinotyping is important for insight into pathophysiology and treatment development. ABSTRACT: Background: Septicaemia with intravascular haemolysis is a rare, but often fatal, presentation of Clostridium perfringens infection. C. perfringens is a Gram-positive, anaerobic bacterium that can produce multiple toxins. Toxinotyping is not performed regularly. Methods: This article describes two human cases of C. perfringens infections. Toxinotyping was performed using polymerase chain reaction (PCR). Additionally, a structured review of the literature was performed which searched specifically for cases of C. perfringens infection with haemolysis. Results: Both cases were identified as toxinotype A strains and both cases were fatal. Also, both cases showed marked haemolysis during their clinical course, which is assumed to have played a significant role in their outcome. In total, 83 references were identified describing human C. perfringens infection with haemolysis. Mortality rates have been stable over the last 10 years at 80%. Toxinotyping has been performed in a total of six cases. Of the four cases analysed by PCR, all were identified as toxinotype A. Conclusions: Haemolytic C. perfringens infections are rare but are fatal in most cases. Toxinotyping is performed rarely. The authors advocate increased use of toxinotyping to gain insight into pathophysiology and more effective interventions.